Short Communication: The utilization and effectiveness test of andisol soil-bioball-Agrobacterium sp. toward heavy metal chrome removal - PRANOTO PRANOTO; RETNO ROSARIASTUTI; ALFIAN PRIHANDOKO (Biodiversitas Journal of Biological Diversity, 2018)
Pranoto, Rosariastuti R, Prihandoko A. 2018. Short Communication: The utilization and effectiveness test of andisol soil-bioball-Agrobacterium sp. toward heavy metal chrome removal. Biodiversitas 19: 1955-1959. This study was aimed to determine chrome metal adsorption and bioremediation ability using andisol soil, bioball, and Agrobacterium sp. The andisol soil characterization was performed by Fourier Transform Infrared Analyzer (FTIR), X-Ray Diffraction (XRD), and Surface Area Analyzer (SAA) while the cell quantity of Agrobacterium sp. was calculated by hemocytometer method. Determination of adsorption and bioremediation effectiveness was done using several parameters such as effect of pH solution, ratio variation of andisol soil-bio ball-Agrobacterium sp, and contact time. The pH variation was ranged from 1-6, while the composition variation of andisol-bioball-Agrobacterium sp. were 2: 0: 0, 1, 5: 1: 5, 1: 2: 10, 0, 5: 3: 15, and 0: 4: 20 (gr: item: mL), and contact time of 30,60,90,120, and 150 minutes. The result of this research shows that the optimum adsorption and bioremediation of Cr metal at pH 5, while the optimum ratio of andisol soil-bioball-Agrobacterium sp was 1, 5: 1: 5 (gr: item: mL), with the contact time for 120 minutes with Cr decrease percentage of 71.3%. The adsorption isotherm followed Langmuir and Freundlich isotherm.